THE CONCEPT OF HOLISTIC MARKETING: THEORETICAL ASPECTS AND FEATURES OF PRACTICAL APPLICATION - Fisun, Yuliia; Marchuk, Valeriya (Socio-economic relations in the digital society, 2023)
This article highlights the topic of using the concept of holistic marketing in the company's activities, which consists of four main elements: internal marketing, integrated marketing, relationship marketing and socially responsible marketing. The main principles of the philosophy of the concept of holistic marketing are considered, as a result of which it is determined that the philosophy of the concept of holistic marketing is based on a common goal, coordinated activities, integrated actions. The main advantages of using holistic marketing are highlighted. Examples of the use of the concept both in the national and in the foreign market are considered. Among the Ukrainian enterprises and organizations that use holistic marketing, there are executive authorities, enterprises that work both in online and offline markets. operate in online and offline markets. The relevance and expediency of applying the concept of holistic marketing in a state of war by small and large businesses are determined. It was determined that the full-scale invasion of the Russian aggressor on the territory of Ukraine had a significant impact on the favorability of Ukrainian businesses to use a complex of targeted marketing in their activities. It has been established that both domestic and foreign enterprises have the experience of using the concept of holistic marketing.
Keywords: holistic marketing; concept; examples of use; relevance; benefits